2000
DOI: 10.1074/jbc.m000469200
|View full text |Cite
|
Sign up to set email alerts
|

GAP1IP4BP Contains a Novel Group I Pleckstrin Homology Domain That Directs Constitutive Plasma Membrane Association

Abstract: The group I family of pleckstrin homology (PH) domains are characterized by their inherent ability to specifically bind phosphatidylinositol 3,4,5-trisphosphate (PtdIns(3,4,5)P(3)) and its corresponding inositol head-group inositol 1,3,4,5-tetrakisphosphate (Ins(1,3,4,5)P(4)). In vivo this interaction results in the regulated plasma membrane recruitment of cytosolic group I PH domain-containing proteins following agonist-stimulated PtdIns(3,4,5)P(3) production. Among group I PH domain-containing proteins, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 44 publications
(32 reference statements)
6
57
0
Order By: Relevance
“…Together, these studies suggest that RASA3 is required to protect circulatlar localization of RASA3. Answering this question, however, has proven to be extremely difficult, even in heterologous cell systems (35,48). Adding to the complexity, recent findings suggest that segregation of PIP 2 and PIP 3 into distinct nanoscale regions in the PM (51) could be another mechanism for regulating the function of RASA3 in resting and in activated platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these studies suggest that RASA3 is required to protect circulatlar localization of RASA3. Answering this question, however, has proven to be extremely difficult, even in heterologous cell systems (35,48). Adding to the complexity, recent findings suggest that segregation of PIP 2 and PIP 3 into distinct nanoscale regions in the PM (51) could be another mechanism for regulating the function of RASA3 in resting and in activated platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors to P2Y12 prevent the inactivation of RASA3, prohibit prolonged RAP1 signaling, and destabilize the growing thrombus. RASA3 is positioned perfectly to prevent unwanted RAP1-dependent platelet activation, as it is targeted to the PM of resting cells by the interaction of its unique PH/BTK domain with phosphatidylinositol 4,5-bisphosphate (PIP 2 ) (47)(48)(49). At sites of vascular injury, however, RASA3 activity in platelets must be reduced to allow for the formation of a hemostatic plug.…”
Section: Discussionmentioning
confidence: 99%
“…97 However, the PH domains of GAP1 m and GAP1 IB4BP bind phosphatidylinositol 3,4,5-triphosphate (PIP 3 ) with high affinity, and GAP1 IB4BP also displays affinity for phosphatidylinositol 4,5-bisphosphate (PIP 2 ). 113 Sequence variations in their PH domains seem to allow selective interaction with particular phosphoinositide head groups. [113][114][115][116] Cytosolic GAP1 m undergoes rapid membrane translocation upon elevation in plasma membrane PIP 3 levels because of activation of cell surface receptors that couple to class I PI3K.…”
Section: Gap1 M and Gap1 Ib4bpmentioning
confidence: 99%
“…113 Sequence variations in their PH domains seem to allow selective interaction with particular phosphoinositide head groups. [113][114][115][116] Cytosolic GAP1 m undergoes rapid membrane translocation upon elevation in plasma membrane PIP 3 levels because of activation of cell surface receptors that couple to class I PI3K. Given the potential role of PI3K in signaling events in lipid rafts, these mechanisms could be involved in N-Ras inactivation and/or the lateral movement of active H-Ras out of lipid rafts.…”
Section: Gap1 M and Gap1 Ib4bpmentioning
confidence: 99%
“…In the case of p50␣, we showed that PTEN inhibition coincides with a defect in downregulation of membrane PI(3,4,5)P 3 levels at late time points after serum stimulation, as determined using the Btk-PH domain. Reduction in membrane PI(3,4,5)P 3 at 90 min is probably due to PTEN activation, as this is the time of maximal PTEN activity, although we cannot rule out the possibility that an increase in phospholipase C activity at 90 min (which would enhance IP4 levels) could also induce Btk-PH detachment from the membrane (57). The observation that p50␣ expression inactivated PTEN would help to explain the functional advantage of tumors with increased levels of p55␥, whose domains are similar to those of p50␣ (58).…”
Section: Discussionmentioning
confidence: 99%